2017
DOI: 10.18632/oncotarget.19474
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Gp120 clade B/C induces a GRP78 driven cytoprotective mechanism in astrocytoma

Abstract: HIV-1 clades are known to be one of the key factors implicated in modulating HIV-associated neurocognitive disorders. HIV-1 B and C clades account for the majority of HIV-1 infections, clade B being the most neuropathogenic. The mechanisms behind HIV-mediated neuropathogenesis remain the subject of active research. We hypothesized that HIV-1 gp120 clade B and C proteins may exert differential proliferation, cell survival and NeuroAIDS effects in human astrocytoma cells via the Unfolded Protein Response, an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
2
8
1
Order By: Relevance
“…After treating cells with gp120 at 100 ng/mL for 10 continuous days we observed an increase in the number of viable cells in all cell lines investigated, including the 965 primary glioma cell line ( Figure 1 A). The gp120 concentration we used has been reported in the literature as effective for inducing signaling in glioma cells and it is also consistent with the gp120 serum concentration in HIV patients [ 32 , 33 ]. A significant difference in cell growth between gp120-treated and untreated cells was not observed at earlier time points (less than 5 days of treatment) ( Supplemental Figure S1A ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…After treating cells with gp120 at 100 ng/mL for 10 continuous days we observed an increase in the number of viable cells in all cell lines investigated, including the 965 primary glioma cell line ( Figure 1 A). The gp120 concentration we used has been reported in the literature as effective for inducing signaling in glioma cells and it is also consistent with the gp120 serum concentration in HIV patients [ 32 , 33 ]. A significant difference in cell growth between gp120-treated and untreated cells was not observed at earlier time points (less than 5 days of treatment) ( Supplemental Figure S1A ).…”
Section: Resultssupporting
confidence: 80%
“…Our results revealed a reduction in the amino acid levels in cells treated with gp120. Together with the reduction in urea ( Table 1 ) and the upregulation of molecules involved in protein synthesis, previously identified by our group [ 32 ], such as the RPS2, RPS13, RPS15 ribosomal proteins and number of initiation and elongation factors as eIF4A1, eIF4G1, PABPC1 and eEFG1, these findings indicate the predominance of anabolic processes over catabolic processes and active protein synthesis. It has been shown that glutamine uptake is essential for growth in a number of cancers [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the case of human immunodeficiency virus 1 (HIV-1), Lopez et al ( 81 ) reported differences in cell survival or apoptosis of U87-MG astrocytoma cells depending on whether the cells were infected by the B or C strains. The authors concluded that this could explain differences in neuropathogenesis induced by the two clades ( 82 ).…”
Section: Glucose-regulated Proteins Grp78 and Grp94 In Viral Infectionmentioning
confidence: 99%
“…HSPA5 was noted to interact with the envelope protein during its folding in the endoplasmic reticulum (Earl et al 1991 ), and other isoforms were implicated to interact with viral proteins like Tat, Gag and Vpr. HIV-1 Clade B gp120 induces HSPA5 and other ER stress markers, as compared to HIV-1 Clade C gp120 in astrocytoma cells (López et al 2017 ). HIV-1 tat is also known to induce HSPA5 and other ER stress markers (Ma et al 2016 ).…”
Section: Hspa Family (Hsp70)mentioning
confidence: 99%